THU0695 The RA FLARE questionnaire (RA-FQ) is responsive to change in ra symptoms and impacts in clinical and observational trials. (15th June 2017) - Bartlett, SJ; Bykerk, VP; Fautrel, B; Guillemin, F; Broeder, A den; Alten, R; Christensen, R; Choy, E; Furst, D; Hewlett, S; Leong, A; March, L; et al.
Abstract : Background: The RA-FQ is a new tool to measure RA flares. We have previously provided evidence of construct validity and reliability.1 Objectives: We evaluated sensitivity to change of the RA-FQ in clinical trials and observational studies of RA patients with low disease activity. Methods: RA patients in observational studies [CATCH-Canada (n=896) and STPR-France (n=138)], and an RCT (DRESS-Netherlands; n=178) completed 5 items asking whether they were in flare (yes/no), and if so, the severity and duration. We selected patients who said they were not in flare and had a DAS28 <3.2 at thefirst visit (V1). Flare at the next study visit (V2) was defined three ways: 1) patient report (yes/no); 2) patient report-stringent (Boolean: patient report yes AND severity ≥4/10 AND duration >7 days [to increase this reflected increased inflammatory disease activity]; and c) DAS definition often used in studies (DAS28<3.2 at V2 required increase of 1.2; DAS≥3.2 at V2 required increase of 0.6). We compared RA-FQ scores with other PROs and disease activity indicators between flaring and non-flaring patients at V2. Effect size was estimatedusing Cohen's SMD. We hypothesized that at V2, RA-FQ scores would be similar in patients not flaring at both visits, and would be significantly higher in those flaring at V2. Results: The mean difference in RA-FQ scores at V2 ranged from 7.3 (95% CI 1.4, 13.2) in STPR (DAS def) to 19.6 (95% CI 16.7, 22.6) in CATCH (patient report-stringent). The standardized mean difference effect sizes (SMDES) ranged from 0.82–1.95, and were largest for patient report-stringent in 2 studies. SMDE were strong (range 0.84–2.42) for patient global, MD global, HAQ, DAS28, and other clinical indicators except ESR. The mean difference in RA-FQ scores at V2 ranged from 7.3 (95% CI 1.4, 13.2) in STPR (DAS def) to19.6 (95% CI 16.7, 22.6) in CATCH (patient report-stringent). The standardized mean difference effect sizes (SMDES) ranged from 0.82–1.95, and were largest for patient report-stringent in 2 studies. SMDE were strong (range 0.84–2.42) for patient global, MD global, HAQ, DAS28, and other clinical indicators except ESR. Conclusions: Data from clinical and observational studies support the responsiveness of the RA-FQ in detecting change over time. The robust psychometric properties of the RA-FQ suggest it reliably detects clinically relevant worsening of RA symptoms consistent with increased disease activity and support its use in research and clinical care. References: Bykerk V et al. RMD Open 2016;2(1):e000225. Disclosure of Interest: None declared